Intestinal Microbiota in Inflammatory Bowel Disease and Carcinogenesis: Implication for Therapeutics. Issue 6 (19th February 2016) - Bruner, SD; Jobin, C
Abstract : Trillions of bacteria inhabit our intestine, forming a community called the microbiota, whose contributions are essential to maintain host homeostasis. Disruption of this normal microbial‐host communication network has deleterious consequences for the host and is associated with intestinal pathologies such as inflammatory bowel diseases (IBD) and colorectal cancer (CRC). Here we present key concepts and mechanisms by which bacteria may participate in intestinal pathology, and discuss possible means to therapeutically target the microbiome.